2022
DOI: 10.3390/jpm12060928
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Single-Site Plus Two-Port Myomectomy versus Conventional Robotic Multi-Port Myomectomy: A Propensity Score Matching Analysis

Abstract: Background: Robotic single-site plus two port myomectomy (RSTM) was designed to reduce the number of incision sites while retaining the advantage of conventional robotic multi-port myomectomy (CRM). This study aimed to explicate RSTM and compare surgical outcomes between it and CRM. Methods: The medical records of 146 patients who had undergone RSTM and 173 who had undergone CRM were reviewed. The surgical outcomes between them were compared by propensity score matching (PSM) analysis. Results: The PSM analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The initial pool of 955 studies, which resulted from the preliminary search of the medical databases, was refined via manual screening of the title and abstract, leading to 107 reports being moved to full-text assessment. Through constant evaluation and strict application of the pre-established inclusion criteria, 53 studies were ultimately included in this review [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. This systematic process of selection is summarised in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The initial pool of 955 studies, which resulted from the preliminary search of the medical databases, was refined via manual screening of the title and abstract, leading to 107 reports being moved to full-text assessment. Through constant evaluation and strict application of the pre-established inclusion criteria, 53 studies were ultimately included in this review [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. This systematic process of selection is summarised in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the visual analogue scale pain score was significantly lower in the RSSM group than in the RMSM group (2.4 ± 0.8 vs. 2.7 ± 0.8, p = 0.0149) [ 16 ]. Furthermore, Won et al reported that the RSSM group had a shorter operative time (148.3 ± 44.8 min vs. 162.3 ± 47.4 min, p = 0.011), lesser decrease in haemoglobin levels (1.8 ± 0.9 g/dL vs. 2.3 ± 1.0 g/dL, p < 0.001), and shorter duration of hospital stay (5.4 ± 0.7 days vs. 5.8 ± 0.7 days, p < 0.001) than the RMSM group [ 17 ]. In our study, the total operative time, docking time, console time, time to manual morcellation, and duration of hospital stay were significantly shorter in the RSSM group than in the RMSM group before 1:1 propensity score matching.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis showed that pain score was significantly lower in the single-port laparoscopic myomectomy group, than in the conventional laparoscopic myomectomy group [ 23 ]. In addition, Ahn et al demonstrated that the post-operative pain score was significantly lower in RSSM than in RMSM (2.7 ± 0.8 vs. 2.4 ± 0.8, p = 0.0149) [ 17 ]. In our study, the duration of hospital stay in the RSSM group was significantly shorter than in the RMSM group (3.12 ± 0.77 days vs. 4.54 ± 1.48, p = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this technique is not ergonomically friendly. To overcome these constraints, a single-site plus additional port platform is a challenging and feasible procedure in gynecological surgery [27,28]. This modified platform reduces the number of incisions, while maintaining the advantages of conventional robotic hysterectomy.…”
Section: Single-site Plus One or Two-port Platformmentioning
confidence: 99%